Fe and 5BDSR based composite fluoropolymer films for THz photonics applications - Ezhov, Dmitry M.; Kochnev, Zahar S.; Fakhrutdinova, Elena D.; Cherepanov, Victor N.; Mamrashev, Alexander A.; Nikolaev, Nazar A.; Svetlichnyi, Valerii A. (Proceedings of SPIE)
We report on the fabrication of free-standing fluoropolymer composite films anisotropic in terms of THz photonic transmission. We used metallic Fe nanoparticles (80-110 nm diameter) obtained by the electric explosion as well as submicron (5 μm average) 5BDSR magnetic alloy particles two-step ground by a ball mill. These particles were dispersed in an acetone solution of the F42-l fluoropolymer. Upon casting, they could be oriented and assembled in alignment with an external magnetic field during solvent evaporation. Oriented composite films of such kind are considered as flexible polarizers with an irregular linear structure. Optical properties in the THz range of spectra were examined using a commercial THz-TDS T-Spec 1000, as well as a custom-made THz-TDS setup with a precise linear polarization of THz emission using a bunch of polarizer and analyzer. In addition, the optical properties of fabricated fluoropolymer composites are compared with copper foiled photoetched polyimide gratings with regular spacing. Irregular structure of magnetophoretic orientated 5BDSR fluoropolymer composites allows using them as ultra-wideband THz polarizers. Single-layer 5BDSR polarizer possesses an extinction ratio within 3:1 to 16:1 in the range of 0.2-2.4 THz.